Structural characterization and adjuvant action of Paulownia tomentosa flower polysaccharide on the immune responses to classical swine fever vaccine in mice - Chen, Xiaolan; Yu, Yaming; Zheng, Yi; Jia, Jiping; Jin, Junjie; Sun, Hongxiang; Jiang, Chunmao; Yang, Haifeng (Frontiers in Veterinary Science, 2023)
Paulownia tomentosa flower polysaccharide (PTFP) from dried cultured P. tomentosa flowers, is widely known for its immunomodulatory activities. Here, PTFP was extracted from Paulownia tomentosa flower using hot water extraction, followed by ethanol precipitation methods. Structural characterization of PTFP was revealed by scanning electron microscope, high-performance anion-exchange chromatography, gel chromatography, ultraviolet and infrared spectral. Meanwhile, adjuvant action of PTFT on the immune responses to classical swine fever vaccine in mice was evaluated to further proclaim the immune regulatory effect of PTFP. The results showed that PTFP was a type of heteropolysaccharide with a dense, rough surface and high molecular weight (667.02 kDa), mainly composed of glucose (30.93%), rhamnose (29.99%), galactose (15.66%), arabinose (6.95%), mannose (5.52%), and xylose (4.80%). The results of gel chromatography suggested that the molecular configuration of PTFP may be a spherical structure. The infrared spectrum results confirmed that the functional groups and chemical bond of PTFP contained -OH, O-H, C-H, C=O, C-O, etc. Moreover, PTFP exhibited obvious immune enhancement effect by improving concanavalin A (ConA), lipopolysaccharide (LPS), and CSFV E2-stimulated splenocyte growth and natural killer cell activity in CSFV-immunized mice. Similarly, the titers of CSFV E2-specific IgG, IgG1, IgG2a, and IgG2b antibodies and IFN-γ and IL-10 levels in CSFV-immunized mice were distinctly increased by PTFP treatment. Overall, PTFP was a macromolecular heteropolysaccharide primarily containing glucose and rhamnose, and possessed the auxiliary effect of immune enhancement on the immune responses to classical swine fever vaccine.